Selected Decisions (4th Ed). (Selected Decisions, 1970)
This paper presents Selected Decisions and Selected Documents' Fourth Issue of the IMF. In order to ensure the uniform application of the relevant Articles of Agreement as they apply to determinations of member's net official holdings of gold and US dollars for the purposes of Article III, Section 3( and )(ii), the IMF adopts or reaffirms several principles of interpretation for the indicated provisions of the IMF Agreement. Each member shall furnish to the IMF the data necessary to determine its net official holdings of gold and United States dollars. The IMF does not intend to apply the rules set forth in II to its holdings of members' currencies having fluctuating rates when there is no practical interest for the IMF or members to do so. In order to avoid misunderstanding, it may be useful to point out that these rules do not constitute a formula for dealing with the currencies of countries in which current transactions are conducted at multiple rates.